Seroprevalence and risk factors analysis of Neospora caninum and Toxoplasma gondii in cattle of Beheira, Egypt - Samy Metwally; Rania Hamada; Kamel Sobhy; Caroline F. Frey; Ragab M. Fereig (Frontiers in Veterinary Science, 2023)
IntroductionNeospora caninum and Toxoplasma gondii are closely related obligate intracellular protozoan parasites. They are considered to be the major causes of infectious abortions and congenital abnormalities in livestock worldwide resulting in huge economic losses. Currently, there are no reports on the prevalence of neosporosis or toxoplasmosis in cattle in Beheira, Egypt's most important region for cattle industry.MethodsThe current study investigated the presence of anti-N. caninum and anti-T. gondii antibodies in apparent healthy cattle from eight localities representing the whole area of Beheira. A total of 358 plasma samples were randomly collected from 6 dairy and 10 beef farms and analyzed by commercially available ELISAs. Production type (dairy versus beef), sex (female vs male), age (< 3 years, 3–5, and > 5 years old), breed (mixed vs Holstein vs Colombian Zebu), and location (various locations) were assessed as risk factors for N. caninum and T. gondii infections.Results and discussionOf the samples, 88 (24.6%) and 19 (5.3%) were positive for anti-N. caninum and anti-T. gondii antibodies, respectively, and mixed infection was detected in 7. Of the 16 herds, 6 dairy and 7 beef herds were positive for antibodies to N. caninum. Antibodies to T. gondii were detected in 4, and 5 of dairy and beef herds, respectively. Production type (dairy) and, therewith, sex (female), age (aged over 5 years), and location were considered as risk factors for N. caninum infection. No factors statistically associated with T. gondii infection were identified. Overall, this study provided the first serological detection of N. caninum and T. gondii infections in cattle from Beheira, demonstrating the endemicity of both parasites in the main cattle rearing region of Egypt. This study also confirmed earlier reports of N. caninum being more present in dairy cattle than in beef cattle. Routine monitoring of N. caninum and T. gondii infections and the implementation of control strategies are urgently needed.